Developing Anti-Bullying Encyclopedia: An Innovative Media to Foster Social Responsibility Attitudes among Primary School Students - Ina Magdalena; Lukman Hakim (UIN Siber Syekh Nurjati Cirebon, 2026)
Background: Bullying in primary schools remains a critical issue, while character education practices often lack structured, literacy-based media that are developmentally appropriate for young learners. Previous studies have primarily emphasized anti-bullying programs or moral instruction without developing systematic instructional media adjusted to lower-grade students. Aims: This study aimed to develop and examine the appropriateness and practical use of an Anti-Bullying Encyclopedia to foster social responsibility attitude among third-grade primary school students. Methods: This research employed a Research and Development (R&D) approach using the ADDIE model (analysis, design, development, implementation, and evaluation). The study was conducted in an elementary school in Tangerang, Indonesia, involving 21 students, one classroom teacher, one media expert, and one material expert. Data were collected through observations, interviews, expert validation questionnaires, and student response questionnaires. Results: The results showed high appropriateness levels, with validation scores of 81.75% (media expert), 80.20% (material expert), and 81.70% (teacher), yielding an overall average of 80.13% (very appropriate). The result of students’ try-out was positive with overall average 76.90 of appropriate category. Conclusions: These findings indicate that the Anti-Bullying Encyclopedia is practical and suitable for classroom use especially for primary school students.